Caravaggio and the Baroque - Caraggio, Michelangelo Merisi da 1573-1610.; Hribar, Mariano Nicora; RCS Editori Rizzoli Coriera (New York, N.Y. RCS Sansoni Editore Spa-Firenze, 1990)
Presents key masterpeices of artistits during the Baroque period like Carravaggio Conegio, lotto Parmigriamino, Tintoretto, Sansoriano, Palladio, Bernini and Benomini.
Based on the book Storia de'll Italliana by Guilio Carlos Argan.
VHS.
Keywords: Scupture, Baroque; Art, Italian; Art, Baroque